Integrated multi-functional morphing aircraft technologies - Santos, Pedro Daniel da Rocha (2018)
Submitted by Paulo Pessoa (pfep@ubi.pt) on 2018-07-04T11:03:06Z No. of bitstreams: 3 autorun.inf: 23 bytes, checksum: b470cbdaf780e98fbd78735abcd4e029 (MD5) vsw.ico: 370070 bytes, checksum: 79cb9c8d527ed203beed8f469b727234 (MD5) PhD_Thesis-PDRSantos.pdf: 55603208 bytes, checksum: 2af4ce5769f82ecc763f63999c84ae39 (MD5)